2020
DOI: 10.1186/s12998-020-00335-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring supervised machine learning approaches to predicting Veterans Health Administration chiropractic service utilization

Abstract: Background: Chronic spinal pain conditions affect millions of US adults and carry a high healthcare cost burden, both direct and indirect. Conservative interventions for spinal pain conditions, including chiropractic care, have been associated with lower healthcare costs and improvements in pain status in different clinical populations, including veterans. Little is currently known about predicting healthcare service utilization in the domain of conservative interventions for spinal pain conditions, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Within our cohort, on average females received 4.9 visits per year and males 4.6 visits and median rates of utilization were 4.3 for females and 4.1 for males, respectively. This is approximately one annual visit higher on average than a previous VHA study, but similarly showed a pattern of higher overall utilization rates among female than male patients [21]. This same study also found that, when strati ed by number of visits, there were more female veterans in the 7 + visit quartile than any of the other three quartiles [21].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Within our cohort, on average females received 4.9 visits per year and males 4.6 visits and median rates of utilization were 4.3 for females and 4.1 for males, respectively. This is approximately one annual visit higher on average than a previous VHA study, but similarly showed a pattern of higher overall utilization rates among female than male patients [21]. This same study also found that, when strati ed by number of visits, there were more female veterans in the 7 + visit quartile than any of the other three quartiles [21].…”
Section: Discussionsupporting
confidence: 64%
“…This is approximately one annual visit higher on average than a previous VHA study, but similarly showed a pattern of higher overall utilization rates among female than male patients [21]. This same study also found that, when strati ed by number of visits, there were more female veterans in the 7 + visit quartile than any of the other three quartiles [21].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…For the topic of health care utilization and costs, 24 articles were included in this review. Most were retrospective cohort studies, 75 76 77 78 79 80 81 82 83 84 85 86 87 while six used prospective cohort studies, 88 89 90 91 92 93 four used a cross-sectional design, 94 95 96 97 and one used a survey for primary data collection. 98 Most studies used the EHR and administrative databases to collect data but three used surveys, 87 96 98 two used public datasets, 78 95 one used mobile phone data, 97 one used images, 90 and one used data from social media.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, AI integration is accelerating in the conventional medical field, and the introduction of AI in complementary and alternative medicine (CAM) is also being attempted (Coleman et al, 2020;Khan et al, 2021). According to the National Health Interview Survey (NHIS) conducted in the United States, 33.2% of adults and 11.6% of children respond they use CAM, and 30% of the medical payments ($14.7 billion) were paid to CAM (Barnes et al, 2004;Barnes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%